Pelatihan Digital Marketing dalam Rangka Peningkatan Kapasitas Ekonomi Masyarakat di Kampung Siwalik - Ahmad Jamaludin Jambunanda; Ipah Latipah; Alkoriyah; Nasehudin; Muhamad Rizki (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Digital Marketing is a strategy for marketing or promoting products through all types of digital media. Mastery of this technology can increase turnover and product sales of Micro, Small and Medium Enterprises (MSMEs) more broadly. However, only a few MSMEs in Kampung Siwalik can use it. The purpose of holding this training is to train MSMEs in Siwalik village to be able to market their products online using digital markets. The method used is observation, interview, presentation and simulation. In the final stage of the training, all MSMEs can create a digital marketing account on the Shopee marketplace and understand how to sell online.